The Effects of a High-Protein Dairy Milk Beverage With or Without Progressive Resistance Training on Fat-Free Mass, Skeletal Muscle Strength and Power, and Functional Performance in Healthy Active Older Adults: A 12-Week Randomized Controlled Trial - Huschtscha, Zoya; Parr, Alexandra; Porter, Judi; Costa, Ricardo J. S. (Frontiers in Nutrition, 2021)
The study aimed to investigate the independent and combined effects of consuming a high protein dairy milk beverage, twice daily, with or without a progressive resistance training (PRT) program on outcomes of age related sarcopenia, in healthy active older (≥50 years) adults. In this 12-week, 2x2 factorial study, participants were randomly allocated into one of four groups: Dairy milk beverage(DM), exercise and dairy milk beverage(EX+DM), exercise alone(EX), and control(CON). The EX group underwent a 12-week whole-body PRT schedule (x3sessions/week) and the high protein dairy milk beverage (DM) was consumed twice daily (30gprotein/day). At week 0, 6, and 12, body composition (iDXA), strength (1-repetition maximum (1RM): leg press, chest press, lateral pull down, and handgrip), power (counter movement jump), cardiorespiratory fitness, and physical performance (gait speed) were measured. Before measures, blood samples were collected to determine immune (i.e., leukocyte trafficking and inflammatory cytokines) and hormonal (i.e.,insulin, cortisol, IGF-1, testosterone, and estradiol) profiles. Participants (n=37) completed the study within the controlled experimental conditions. Protein intake increased in EX+DM(mean±SD:1.2±0.2 to 1.8±0.4g/kgBM/day) and DM(1.3±0.5 to 1.8±0.6g/kgBM/day) groups during the intervention. Absolute fat-free mass increased in EX+DM (mean [95% confidence interval]:0.65[0.25,1.0] kg) and EX(0.49[-0.44,1.40] kg) groups (P<0.001), compared to DM(-0.54[-1.6,0.05] kg). Relative fat mass decreased (group*time, P=0.018) in DM(-1.8[-3.3,-0.35] %) and EX+DM(-1.3[-2.3,-0.31] %), which was a greater reduction than the control (CON)(0.10[-0.80,1.0] % group (P<0.01). Relative maximal strength increased in both EX and EX+DM(≥35%;P<0.05) groups, but not in DM and CON groups. The change in 1RM strength outcomes was higher in EX+DM compared to all other groups (53-78%;P<0.01). There was an increase in resting plasma IL-10 concentration in EX+DM (88%), compared to all the other groups (P=0.016). No other differences in systemic inflammatory cytokines were observed. There were no significant changes in all hormone concentrations measured between all groups. In conclusion high protein dairy milk beverage providing additional protein did not further enhance the effects of PRT on outcomes of fat-free mass, power, or physical performance. However, there was a significant augmentative effect for high protein dairy milk consumption on changes to maximal strength outcomes during PRT in healthy active older adults.